The DUF506 Gene Family in Triticum aestivum: Genome-Wide Identification and Expression Profiling Under Salt Stress - Yueduo Wang; Shuotong Liu; Taiyu Lin; Shenglong Kan; Pei Yu (Agronomy)
As a subfamily of the PD-(D/E)XK nuclease superfamily, DUF506 family shows great potential in abiotic stress responding of higher plant, yet its clues of structure, evolution and functions remain largely unexplored due to their distant phylogenetic relationship with other nuclease families, especially in Triticum aestivum. In this study, 26 T. aestivum DUF506 genes (TaDUF506) were identified from genome-wide level through bioinformatic techniques. Phylogenetic and structural analyses revealed that TaDUF506 genes exhibit conserved motif and gene structure patterns intra-phylogenetic clusters but display significant divergence inter-clusters. Gene duplication identification showed that whole-genome duplication event (WGD) was the primary driver of TaDUF506 family expansion, while Ka/Ks analysis indicated that whole TaDUF506 family experienced purifying selection generally. Gene ontology analysis and protein-protein interaction prediction suggested that DUF506 plays a potential role in transcription regulation and nucleotide-excision generally. Promoter analyses highlighted an enrichment of hormone-responsive elements linked to salt stress in TaDUF1.3-3D TaDUF5.1-3A, with expression analysis demonstrated their significant upregulation under salt stress, suggesting the potential roles in stress responses. Altogether, our study advances the understanding of DUF506 gene family in higher plant from structural, evolutional and functional aspects, and thereby provides a foundation for the development of salt-tolerant wheat varieties.